Mapping organizational culture in the context of a circular economy: a case study for a Brazilian company - Ferreira, Camila dos Santos; Gomes, Giovana Monteiro; Natalense, Julio Cesar; Roiz, Guilherme Augusto; Ometto, Aldo Roberto; Gerolamo, Mateus Cecílio (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – This study aims to answer the following question: “Which organizational culture is embedded in a company that adopts a circular business model?” Theoretical framework – Although the circular economy is gaining a lot of attention from the academia recently, the literature has not been able to address the complexity inherent to this transition from the linear to the circular approach, regarding both a change in the organization and mindset. Design/methodology/approach – The Organizational Culture Assessment Instrument (OCAI) was chosen to identify the culture of the company and its values. The company selected was already in the CE100 network in Brazil so is a best-case scenario to be studied. Findings – The findings show that this company can behave in a way to promote innovation and focus on product development, which are characteristics of the Adhocracy culture profile. The organization also shows a desire to let go of formal and structured processes and embrace behavior that enhance collaboration and teamwork, which are important features of circular businesses. The study concludes that the OCAI methodology was able to show tendencies related to circular businesses. Research, Practical & Social implications – The study is limited since the OCAI method is only applied to one organization. As such, the authors suggest that other organizations be studied. Originality/value – The study discusses the importance of organizational culture and its relationship with the circular economy. Keywords: Circular Economy; Change Management; Culture; Circular Business Model.